Model Pengabdian Terintegrasi Mahasiswa KKN dalam Meningkatkan Literasi Pendidikan, Tata Kelola Administrasi, dan Digitalisasi Informasi Dusun Waru, Samigaluh, Kulon Progo - Retna Mega Kartika; Ardiyanto, Bagas; Krijthe, Frida Alandia; Khoirunnisa, Herwinda; Hapsari, Ismaya Candra; Marlin, Adinda Agesti; Nuryanti, Avi; Agustin, Revita; Azman, Adry Mohammad; Mubaarok, Dzaki; Muchran, Murniady (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This article aims to describe the implementation of an integrated community service model conducted by KKN students to enhance educational literacy, administrative governance, and digital information systems in Dusun Waru, Samigaluh, Kulon Progo. The method employed a participatory approach consisting of socialization, planning, implementation, and evaluation stages based on social reflection. The programs included interactive learning media and learning motivation sessions for elementary students, assistance in school and TPA accreditation preparation, administrative data collection for residents and Posbindu, early marriage awareness socialization, compost-making training, renewal of administrative signboards, and the development of an official village website. The results indicate increased student learning enthusiasm, improved administrative order, enhanced institutional readiness for accreditation, and the establishment of a website to support transparency and public information access. This integrated service model effectively strengthens community capacity in educational, administrative, and digital aspects and has the potential to be replicated in similar rural contexts.